Use dependent limb dominence and somatosensory evoked potentials (SEPs) in the congenitally blind - Dayananda Giriyappa; Roopakala M. Subramanyam; Rajeev Sharma; Srinivasa Rangasetty (Al Ameen Medical College, 2013)
Background and purpose: Vision has been considered as the dominant modality in the human multi-sensory perception of the surroundings. The congenitally blind individuals use cortical areas that are normally reserved for vision during Braille reading. Use-dependent reorganization and neural plasticity changes occur as a consequence of many events, including the normal development and maturation of the organism, the acquisition of new skills. The research was designed to study the effect of blindness on SEPs in the dominant hand (Braille reading hand) compared to the non dominant (non Braille reading hand) in the congenitally blind. Material and methods: SEPs were recorded in 15 Braille reading congenitally blind females and compared with 15 age matched normal sighted females following right and left index finger stimulation. Latency and amplitudes of SEP waveforms (N9, N13, and N20) were measured. Results: The SEP-N20 amplitude was significantly increased in the congenitally blind (p < 0.0001 for right index finger and p < 0.005 for left index finger). There is a very large effect of blindness (3.11) on right index finger. Conclusions: The congenitally blind individuals have larger N20 amplitude, which is suggestive of greater somatosensory cortical activity. Effect of blindness and Braille reading skills is greater on SEPs recorded from the dominant and preferred hand. A varied contribution from Basic mechanisms in plasticity like neurogenesis, activity-dependent synaptic and neuronal plasticity may be involved.